Anticipatory effects on lower extremity kinetics during a land and cross step maneuver in female volleyball players - Richwalski, B.; Wang, H.; Hankemeier, D.; Avedesian, J. M.; Judge, L. W.; Dickin, D. C. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Anticipation has been previously shown to affect lower extremity mechanics during both landing and cutting maneuvers. However, little research has been conducted looking at the effects of anticipation on lower body kinetics and kinematics during a land and cross step maneuver, which due to similar kinematics, may elicit injury. The purpose of this study was to investigate competitive female volleyball players and the effect of anticipation on lower extremity mechanics during a landing and subsequent cross stepping maneuver. METHODS: Twelve female, college-level volleyball players performed right and left cross step maneuvers following a landing under anticipated and unanticipated conditions. Kinetics were measured for the ankle, knee and hip of the dominant limb during the landing phase of the land and cross step anticipatory conditions. RESULTS: An interaction effect (anticipation x direction; P=0.001) was observed for vertical ground reaction force (VGRF), in which greater VGRF was found during unanticipated pivoting maneuvers. Additional interaction effects were determined for ankle (P=0.004) and hip (P=0.037) power absorption, in which greater absorption was found during anticipated, push off conditions. Frontal plant knee kinetics revealed a higher-order interaction, as a larger knee adduction moment was shown during anticipated, push off trials (P=0.001). CONCLUSIONS: High risk cross step maneuvers were found during unanticipated and anticipated conditions, as athletes demonstrated movement mechanics that may increase the risk of knee injury when performing movements away from the dominant limb. Consideration should be given to drills familiarizing volleyball players with unanticipated and anticipated changes of direction, as well as improving strength of the lower extremity muscles required to effectively decelerate the body, as both training modalities may minimize injury risk during cross step maneuvers.